Skeletal myofiber vascular endothelial growth factor is required for the exercise training‐induced increase in dentate gyrus neuronal precursor cells. (28th June 2017) - Rich, Benjamin; Scadeng, Miriam; Yamaguchi, Masahiro; Wagner, Peter D.; Breen, Ellen C.
Abstract : Key points: Peripheral vascular endothelial growth factor (VEGF) is necessary for exercise to stimulate hippocampal neurogenesis. Here we report that skeletal myofiber VEGF directly or indirectly regulates exercise‐signalled proliferation of neuronal precursor cells. Our results found skeletal myofiber VEGF to be necessary for maintaining blood flow through hippocampal regions independent of exercise training state. This study demonstrates that skeletal myofiber VEGF is required for the hippocampal VEGF response to acute exercise. These results help to establish the mechanisms by which exercise, through skeletal myofiber VEGF, affects the hippocampus. Abstract: Exercise signals neurogenesis in the dentate gyrus of the hippocampus. This phenomenon requires vascular endothelial growth factor (VEGF) originating from outside the blood–brain barrier, but no cellular source has been identified. Thus, we hypothesized that VEGF produced by skeletal myofibers plays a role in regulating hippocampal neuronal precursor cell proliferation following exercise training. This was tested in adult conditional skeletal myofiber‐specific VEGF gene‐ablated mice (VEGF HSA−/− ) by providing VEGF HSA−/− and non‐ablated (VEGF f/f ) littermates with running wheels for 14 days. Following this training period, hippocampal cerebral blood flow (CBF) was measured by functional magnetic resonance imaging (fMRI), and neuronal precursor cells (BrdU+/Nestin+) were detected by immunofluorescence. The VEGF f/f trained group showed improvements in both speed and endurance capacity in acute treadmill running tests ( P < 0.05). The VEGF HSA−/− group did not. The number of proliferating neuronal precursor cells was increased with training in VEGF f/f ( P < 0.05) but not in VEGF HSA−/− mice. Endothelial cell (CD31+) number did not change in this region with exercise training or skeletal myofiber VEGF gene deletion. However, resting blood flow through the hippocampal region was lower in VEGF HSA−/− mice, both untrained and trained, than untrained VEGF f/f mice ( P < 0.05). An acute hypoxic challenge decreased CBF ( P < 0.05) in untrained VEGF f/f, untrained VEGF HSA−/− and trained VEGF HSA−/− mice, but not trained VEGF f/f mice. VEGF f/f, but not VEGF HSA−/−, mice were able to acutely run on a treadmill at an intensity sufficient to increase hippocampus VEGF levels. These data suggest that VEGF expressed by skeletal myofibers may directly or indirectly regulate both hippocampal blood flow and neurogenesis. Key points: Peripheral vascular endothelial growth factor (VEGF) is necessary for exercise to stimulate hippocampal neurogenesis. Here we report that skeletal myofiber VEGF directly or indirectly regulates exercise‐signalled proliferation of neuronal precursor cells. Our results found skeletal myofiber VEGF to be necessary for maintaining blood flow through hippocampal regions independent of exercise training state. This study demonstrates that skeletal myofiber VEGF is required for the hippocampal VEGF response to acute exercise. These results help to establish the mechanisms by which exercise, through skeletal myofiber VEGF, affects the hippocampus.